Predictors for caesarean delivery and neonatal admission after trial of labour in women with one previous lower segment caesarean scar - Tan, P.C.; Subramaniam, R.N.; Omar, S.Z. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
Predictors for emergency caesarean delivery and neonatal admission following a trial of labour can be identified. This information should be incorporated into the counselling of women contemplating a trial of labour. The strongest predictor for neonatal admission was emergency caesarean delivery, further emphasising the need for careful case selection in a trial of labour to minimise the risk of failure.